2004
DOI: 10.1104/pp.104.051060
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic Reticulum, Oleosins, and Oils in Seeds and Tapetum Cells

Abstract: Diverse organisms contain neutral lipids in subcellular particles for food reserves and other purposes. These lipid particles are present in seeds, flowers, pollen and fruit of higher plants, the vegetative and reproductive organs of primitive plants, algae, fungi, nematodes, mammalian glands and brown adipose tissue of mammals, and bacteria. Of all these lipid particles, the oil bodies (OBs) in seeds are the most prominent and best studied.Seeds of most plant species store oils (triacylglycerols [TAGs]) as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

7
166
2
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 192 publications
(179 citation statements)
references
References 38 publications
7
166
2
4
Order By: Relevance
“…The one-cell-layer gametophyte could be observed easily with confocal microscopy for the subcellular OBs and other structures. Transient expression of various gene constructs transformed into gametophyte cells revealed that all OBs were linked to the endoplasmic reticulum (ER), that oleosins were synthesized in extended regions of the ER, and that two different oleosins were colocated in all OBs.Eukaryotes and prokaryotes contain neutral lipids in subcellular droplets as food reserves and/or for other purposes (Hsieh and Huang, 2004;Martin and Parton, 2006;Goodman, 2008;Rajakumari et al, 2008). These lipid droplets are present in seeds, pollens, fruits, and flowers of higher plants; the vegetative and reproductive organs of lower plants, algae, fungi, and nematodes; mammalian organs/tissues, such as mammalian glands and adipose tissues; and bacteria.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…The one-cell-layer gametophyte could be observed easily with confocal microscopy for the subcellular OBs and other structures. Transient expression of various gene constructs transformed into gametophyte cells revealed that all OBs were linked to the endoplasmic reticulum (ER), that oleosins were synthesized in extended regions of the ER, and that two different oleosins were colocated in all OBs.Eukaryotes and prokaryotes contain neutral lipids in subcellular droplets as food reserves and/or for other purposes (Hsieh and Huang, 2004;Martin and Parton, 2006;Goodman, 2008;Rajakumari et al, 2008). These lipid droplets are present in seeds, pollens, fruits, and flowers of higher plants; the vegetative and reproductive organs of lower plants, algae, fungi, and nematodes; mammalian organs/tissues, such as mammalian glands and adipose tissues; and bacteria.…”
mentioning
confidence: 99%
“…Eukaryotes and prokaryotes contain neutral lipids in subcellular droplets as food reserves and/or for other purposes (Hsieh and Huang, 2004;Martin and Parton, 2006;Goodman, 2008;Rajakumari et al, 2008). These lipid droplets are present in seeds, pollens, fruits, and flowers of higher plants; the vegetative and reproductive organs of lower plants, algae, fungi, and nematodes; mammalian organs/tissues, such as mammalian glands and adipose tissues; and bacteria.…”
mentioning
confidence: 99%
See 3 more Smart Citations